(untitled) (Homoeopathy for All, 2023)
Each year, a significant number of individuals over the globe experience the widespread ailment referred to as "Eye Flu." However, following a recent epidemic of conjunctivitis in Delhi, it is crucial to do a comprehensive analysis of the tactics employed for its management. Homeopathic clinics in Delhi NCR witnessed many such cases and treated them successfully in a short span of time. The surge in cases closely correlated with heavy rainfall, waterlogging and floods underscoring